The Rise of the School District Chief Equity Officer: Moving Beyond Mimetic Isomorphism and Promoting Anti-Racist Systemic Change. (February 2023) - Lewis, Maria M.; Modeste, Marsha E.; Johnson, Royel M.
Purpose: A growing number of school districts have recently added a position to the superintendent's cabinet, often titled chief equity officer. While the chief equity officer position is still in its early stages, we have an opportunity to examine insights from this work in the higher education context—both to support the adoption and implementation of the position, and the change work the chief equity officer will lead throughout the organization. The following conceptual question guides our analytical review: How can the role of chief equity officer be meaningfully and thoughtfully adapted for K-12 schools and districts in a critical anti-racist manner? Moverover, how might insights from higher education and scholarly knowledge on the nature of educational institutions, change within organizations, leadership practice, and learning inform the development of this role?Proposed Conceptual Argument: While the chief equity officer position was initially developed in response to historic and systemic inequities, over time, as this position becomes standardized through a process scholars call mimetic isomorphism, it runs the risk of becoming symbolic, only serving to signal an organization's commitment to equity-oriented work without meaningfully attending to its structures for learning, policies, or practices.Implications: Chief equity officers have a formal role within the district; however, their work requires an organizational commitment, from educators and educational leaders, for anti-racist systemic change. Structural, financial, and personnel-oriented supports are critical. Training programs for educators and leaders should thoughtfully prepare future chief equity officers, and continue to extend existing efforts to prepare anti-racist, equity-oriented principals, superintendents, teachers, and other educational leaders.